2020
DOI: 10.1021/acs.jpca.0c07860
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Covalent versus Spin–Orbit Coupling Contributions to Temperature-Dependent Electron Spin Relaxation in Cupric and Vanadyl Phthalocyanines

Abstract: Recent interest in transition-metal complexes as potential quantum bits (qubits) has reinvigorated the investigation of fundamental contributions to electron spin relaxation in various ligand scaffolds. From quantum computers to chemical and biological sensors, interest in leveraging the quantum properties of these molecules has opened a discussion of the requirements to maintain coherence over a large temperature range, including near room temperature. Here we compare temperature-, magnetic field position-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…29 To illustrate the power of this approach in understanding spin-phonon coupling contributions to decoherence in molecular qubits, we turn to a comparison between vanadyl phthalocyanine (VOPc) and copper phthalocyanine (CuPc) (Figure 1A). 19 with D2d CuCl4 2possessing more spin-phonon coupling than D4h CuCl4 2owing to a greater number of totally symmetric modes. 22 Though totally symmetric vibrational modes dominate 0 coupling for both VOPc and CuPc, the change in point group between C4v and D4h nonetheless has important consequences for spin-phonon coupling.…”
Section: Results and Analysismentioning
confidence: 98%
“…29 To illustrate the power of this approach in understanding spin-phonon coupling contributions to decoherence in molecular qubits, we turn to a comparison between vanadyl phthalocyanine (VOPc) and copper phthalocyanine (CuPc) (Figure 1A). 19 with D2d CuCl4 2possessing more spin-phonon coupling than D4h CuCl4 2owing to a greater number of totally symmetric modes. 22 Though totally symmetric vibrational modes dominate 0 coupling for both VOPc and CuPc, the change in point group between C4v and D4h nonetheless has important consequences for spin-phonon coupling.…”
Section: Results and Analysismentioning
confidence: 98%
“…The well‐studied class of V(IV) qubits contain experimental examples in each of the three decoherence regimes, providing an instructive conceptual comparison. The electron spin relaxation of vanadyl phthalocyanine (VOPc) has been studied in a glassy frozen solution, [59] a pure crystalline solid, [38] and diamagnetically diluted crystalline dispersions in titanyl phthalocyanine (TiOPc) host at 1 : 10, 1 : 100, and 1 : 1000 concentrations [38,49] . At 300 K in 1 : 10 dilution, VOPc exists in the spin‐spin regime, where T M is significantly smaller than T 1 owing to electronic dipolar contributions to decoherence.…”
Section: Spin‐spin and Motional Contributions To Decoherencementioning
confidence: 99%
“…The interplay between factors in the dynamic ligand field model can be illustrated by recent studies comparing Cu(II) and V(IV) S=1/2 qubit candidates [49,62] . It was experimentally shown that the T 1 of vanadyl phthalocyanine (VOPc) is longer than that of copper phthalocyanine (CuPc) at higher temperatures (>25 K) where the spin‐phonon regime dominates, [49] with VOPc exhibiting coherence up to room temperature [38] . These results can be rationalized and quantitatively understood using the spin‐phonon coupling factors found in Equation 5: (1) the energy of the ligand field excited state that spin‐orbit couples with the ground state, (2) the covalencies of the ligand‐metal bonds, and (3) the spin‐orbit coupling constant.…”
Section: Dynamic Ligand Fields In Electron Spin Qubitsmentioning
confidence: 99%
See 2 more Smart Citations